2020
DOI: 10.3390/ma13214711
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Laser Shock Peening on Fretting Fatigue Life of TC11 Titanium Alloy

Abstract: The purpose of this paper is to investigate the performance of laser shock peening (LSP) subjected to fretting fatigue with TC11 titanium alloy specimens and pads. Three laser power densities (3.2 GW/cm2, 4.8 GW/cm2 and 6.4 GW/cm2) of LSP were chosen and tested using manufactured fretting fatigue apparatus. The experimental results show that the LSP surface treatment significantly improves the fretting fatigue lives of the fretting specimens, and the fretting fatigue life increases most when the laser power de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Temperature and load promote the formation of GND and facilitate crack nucleation and propagation. Yang et al [33] improved the fretting fatigue life of TC11 titanium alloy by laser shock peening, and suggested that the fretting fatigue cracks were mainly nucleated in β phase. Zhang et al [34] investigated the effect of laser quenching on the fretting fatigue properties of TC11 titanium alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature and load promote the formation of GND and facilitate crack nucleation and propagation. Yang et al [33] improved the fretting fatigue life of TC11 titanium alloy by laser shock peening, and suggested that the fretting fatigue cracks were mainly nucleated in β phase. Zhang et al [34] investigated the effect of laser quenching on the fretting fatigue properties of TC11 titanium alloy.…”
Section: Introductionmentioning
confidence: 99%
“…The variation in the elastic modulus of the hardened layer was also taken into consideration. Yang et al [26] looked at how TC11's fretting fatigue properties were affected by laser impact strengthening. The findings of the experiment demonstrated that the specimens' fretting fatigue life was greatly increased by the laser surface treatment, with the highest improvement occurring at 4.8 GW/cm 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Such textured polymer surfaces decorated with Ag NPs can be prospective antimicrobial coatings. Another example of laser-induced physical phenomena is laser shock peening, demonstrating significantly improving the fretting fatigue life of TC11 titanium alloy [ 14 ]. In the article by Piotr Kupracz et al [ 15 ] laser re-solidification was demonstrated as an approach for the modulation of morphology and structure of metal-decorated TiO 2 nanotubes to obtain visible light harvesting.…”
mentioning
confidence: 99%